2024
DOI: 10.3390/met14030308
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Resistance Spot Welding for Grade 2 Titanium Alloy: Experimental Investigation and Artificial Neural Network Modeling

Marwan T. Mezher,
Diego Carou,
Alejandro Pereira

Abstract: The resistance spot welding (RSW) process is still widely used to weld panels and bodies, particularly in the automotive, railroad, and aerospace industries. The purpose of this research is to examine how RSW factors such as welding current, welding pressure, welding time, holding time, squeezing time, and pulse welding affect the shear force, micro-hardness, and failure mode of spot welded titanium sheets (grade 2). Resistance spot welded joints of titanium sheets with similar and dissimilar thicknesses of 1–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The tensile shear test concluded that the greatest shear force for all welded specimens was 378.25 N and that they all failed in an interfacial failure (IF) mode. Mezher et al [35] analyzed the RSW of the grade 2 titanium alloy using experimental and ANN investigations. Utilizing an ANN, Martin et al [36] forecasted how AISI 304's RSW parameters would affect the material's pitting corrosion behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile shear test concluded that the greatest shear force for all welded specimens was 378.25 N and that they all failed in an interfacial failure (IF) mode. Mezher et al [35] analyzed the RSW of the grade 2 titanium alloy using experimental and ANN investigations. Utilizing an ANN, Martin et al [36] forecasted how AISI 304's RSW parameters would affect the material's pitting corrosion behavior.…”
Section: Introductionmentioning
confidence: 99%